The Current Landscape of Antibiotic Resistance of Salmonella Infantis in Italy: The Expansion of Extended-Spectrum Beta-Lactamase Producers on a Local Scale - Di Marcantonio, Lisa; Romantini, Romina; Marotta, Francesca; Chiaverini, Alexandra; Zilli, Katiuscia; Abass, Anna; Di Giannatale, Elisabetta; Garofolo, Giuliano; Janowicz, Anna (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Infantis is one of the five main causes of human salmonellosis in EU and in recent years, has been increasingly reported to carry multiple antimicrobial resistance determinants, including extended-spectrum beta-lactamase (ESBL) genes. In our study, we used WGS-based tools to characterize S. Infantis strains circulating in Abruzzo and Molise regions Italy between 2017 and 2020 and to compare this local dataset to the S. Infantis population present in Italy in the last two decades. Phylogenetic analyses demonstrated that majority of strains isolated from poultry and turkeys from Abruzzo and Molise were closely related, and belonged to one of the two main genetic clusters present in Italy, which grouped predominantly ESBL-producing strains that harbored pESI-like plasmid. We showed that 60 % of the local strains carried multiple antibiotic resistance genes, including ESBL gene blaCTX-M-1 as well as aadA1, dfrA1, dfrA14, sul1 and tet(A) genes present on the pESI-like megaplasmid. The analysis of strains from Abruzzo and Molise and the publicly available Italian S. Infantis sequences revealed a dramatic increase in the number of identified AMR genes in the strains isolated after 2011. Moreover, the number of strains resistant to five or more antibiotic classes increased from 20 % to 80 % in the last decade likely due to the acquisition of the megaplasmid. The persistence of the ESBL-producing and the multidrug-resistant clone of S. Infantis in poultry populations in Italy and in Europe requires rapid and efficient intervention strategies to prevent further expansion of the clone.